Three Gorges project: the largest water conservancy project in the world - Jiazhu, Wang (2002)
The Three Gorges Project (TGP) is the largest water conservancy project ever built in China and in the world. Construction of TGP commenced in 1993 and more than half is complete. It is predicted that the project will be put into initial use in 2003, and finished in 2009. This article discusses the project's advantages and some of the challenges faced, including technical, environmental and resettlement issues. - Reproduced.
Keywords: Water conservation